Quantitative analysis of tree species in two community forests of Dolpa district, mid-west Nepal - Kunwar, Ripu M; Sharma, Shiv P (Himalayan Journal of Sciences, 2006)
Two community forests, Amaldapani and Juphal from Dolpa district, were selected for a study of quantitative analysis of tree flora. A total of 419 individual trees representing 16 species, 16 genera and 11 families were recorded. Total stand density and basal area were, respectively, 2100 trees ha-1 and 90 m2ha-1 in Amaldapani and 2090 tree ha-1 and 152 m2ha-1 in Juphal. Of the families, the Pinaceae was the most diverse, with 28 individuals representing five species and five genera, followed by the Rosaceae with three individuals representing two species and two genera. Pinus wallichiana, Abies spectabilis, Quercus semecarpifolia and Cedrus deodara had the highest importance value index and could therefore be considered the dominant species. Since the study area was diverse in tree population of conifers and deciduous forest tree species, it is essential to carry out further studies in order to establish conservation measures that will enhance local biodiversity. Key words: Vegetation, tree species, Pinus wallichiana, community forest, Dolpa Himalayan Journal of Sciences 2(3): 23-28, 2004